2015
DOI: 10.1016/j.cgh.2015.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Sofosbuvir and Daclatasvir in Patients With Fibrosing Cholestatic Hepatitis C After Liver Transplantation

Abstract: Sofosbuvir therapy with daclatasvir or ribavirin leads to major clinical improvement and high rates of sustained virologic response at week 12 in most patients with recurrence of HCV infection and FCH after liver transplantation. ClinicalTrial.gov no: NCT01944527.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
82
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(96 citation statements)
references
References 24 publications
9
82
0
5
Order By: Relevance
“…10,11 Recently, combination of sofosbuvir and daclatasvir or ledipasvir with or without ribavirin has been used in this condition with a 96-100% success rate. [12][13][14] In our series, all patients achieved SVR 12 on 24 weeks treatment of sofosbuvir and ribavirin. We conclude that a combination of sofosbuvir and ribavirin for 24 weeks results in a high cure rate of severe HCV recurrence including FCH after solid organ transplant.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…10,11 Recently, combination of sofosbuvir and daclatasvir or ledipasvir with or without ribavirin has been used in this condition with a 96-100% success rate. [12][13][14] In our series, all patients achieved SVR 12 on 24 weeks treatment of sofosbuvir and ribavirin. We conclude that a combination of sofosbuvir and ribavirin for 24 weeks results in a high cure rate of severe HCV recurrence including FCH after solid organ transplant.…”
Section: Discussionmentioning
confidence: 54%
“…Recent reports suggest successful treatment of FCH with response rates and survival rates of 80-100% with the use of sofosbuvir-based regimens. [10][11][12][13][14] We report 4 cases of acute severe HCV recurrence after transplantation including 3 with FCH (3 after liver transplant and 1 after kidney transplant), and successful treatment of these patients with sofosbuvir and ribavirin.…”
mentioning
confidence: 99%
“…37 In a study of 23 FCH patients, 15 patients received sofosbuvir plus daclatasvir and 8 patients received sofosbuvir plus ribavirin. 38 Rapid and dramatic clinical improvement was noted with 24 weeks of therapy without the need for liver retransplantation. Interestingly, although the rapid virologic response rates were low, 96% of the treated patients achieved SVR12.…”
Section: Fibrosing Cholestatic Hepatitismentioning
confidence: 98%
“…Several IFN-free regimens have become available for daily practice, and most studies have demonstrated high SVR rates and good safety outcomes [3,4]. Some IFN-free regimens have demonstrated favorable safety and high eicacy within clinical trials among dificult-to-treat patients such as patients who have experienced DAA treatment, cirrhosis, chronic kidney disease, Human immunodeiciency virus co-infection, those on opiate agonist therapy, and patients with liver transplant [5][6][7][8][9][10]. However, most clinical trials of IFN-free therapy for chronic hepatitis C have excluded hepatitis B virus (HBV) coinfection.…”
Section: Introductionmentioning
confidence: 99%